REKONSTRUKSI PARADIGMA PENANGGULANGAN STUNTING : INTERNALISASI NILAI-NILAI QUR’ANI SEBAGAI UPAYA PENGUATAN MORAL ORANG TUA - Maudy Muzalifah Azzahra; Bashori (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2026)
Stunting remains a crucial challenge for human resource development in Indonesia, despite the massive implementation of various medical technocratic policies. The low effectiveness of nutritional interventions in the field is often triggered by sociocultural factors and a lack of profound parental awareness regarding children's developmental rights. This study aims to reconstruct the stunting prevention paradigm through an Islamic theological approach by internalizing Quranic values as a basis for parenting motivation. Employing a descriptive qualitative method with a literature study and thematic exegesis (tafsir) approach, this research proposes the concept of "Health Eschatology" based on Surah An-Nisa verse 9. The results indicate that preventing the birth of a weak generation (dzurriyyatan dhi’afan) is not merely a medical recommendation but a theological mandate with eschatological consequences before God. Furthermore, the application of "Nutritional Theology" through the optimization of lactation (QS. Al-Baqarah: 233) and the fulfillment of food that is not only halal but also thayyib (QS. Al-Baqarah: 168) provides technical guidance aligned with the concept of the First 1000 Days of Life. These findings emphasize that integrating spiritual values into public health policies can serve as a catalyst for more consistent parental behavioral change. This paradigm reconstruction is expected to transform stunting prevention motivation from mere administrative compliance into a social piety movement to realize a superior and high-quality generation.